Petri Net Implementation of Cell Signaling for Cell Death - SHRUTI JAIN; PRADEEP K. NAIK; SUNIL V. BHOOSHAN (International Journal of Pharma and Bio Sciences, 2010)
This paper demonstrates the steps of a new integrating methodology to develop and analyze models of biological pathways in a systematic manner using well established Petri net technologies. The whole approach comprises stepwise modeling, animation, model validation as well as qualitative and quantitative analysis for behavior prediction. After a short introduction into systems biology we demonstrate how to develop and validate qualitative models of biological pathways in a systematic manner using the well-established Petri net analysis technique of place and transition invariants. This work examines signaling networks that control the survival decision treated with combinations of three primary signals, tumor necrosis factor-α (TNF), epidermal growth factor (EGF) and insulin. The example used in this paper is devoted to apoptosis, the genetically programmed cell death. Apoptosis is an essential part of normal physiology for most metazoan species. Disturbances in the apoptotic process could lead to several diseases. The signal transduction pathway of apoptosis includes highly complex mechanisms to control and execute programmed cell death.